MATEMÁTICA E ARTES: ANAMORFISMO NO ENSINO INTERDISCIPLINAR DE GEOMETRIA - Silva, Jonathan de Aquino da (2023)
This thesis stems from the recognition of high school students' difficulties in solving visualization-related exercises in the National High School Examination (ENEM). Building upon the master's dissertation theme, some inquiries persisted, and interdisciplinary work may address some uncertainties and enhance students' experience with the proposed thesis topic. The general objective of this study is to analyze how high school students establish connections between Geometry and Arts through the exploration of anamorphisms and answer the following question: How can high school students establish relationships between Geometry and Arts using anamorphisms? To achieve this purpose, specific objectives were outlined, including the development of anamorphisms using manual and technological resources; investigating the mathematical content underlying the creation of these visual representations; analyzing the anamorphisms produced by students; promoting the development of geometric visualization in everyday objects and figures; fostering interdisciplinary activities between Mathematics and Arts through anamorphisms; and finally, evaluating participants' feedback regarding their learning. The deformations presented utilize and revisit content preceding the one developed with the investigated group, i.e., third-year high school students from a private school where the doctoral candidate is the effective teacher in the city of Santa Maria. The work is a case study, adopting a qualitative approach, and student feedback on the work also served as an evaluation method for the research to be conducted. The stimulation of creativity and the realization that mathematical visualization can be developed in unconventional ways were the main results concluded by the students.